Development of a method to transfer a quorum-sensing inhibiting gene construct into a Vibrio parahaemolyticus strain - Thi Thu Huyen, Nguyen; Thi Thu Thuy, Nguyen; The Hai, Pham (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2SDO - 10.25073/2588-1140/vnunst.4619, 2017)
In recent years, aquaculture in Vietnam has been expanding and becoming an important domestic economic sector. However, diseases of aquaculture animals are always a great threat to this industry. Vibrios - a group of aquatic bacterial pathogens, are known for causing serious diseases (vibriosis) and killing aquatic organisms. Due to the long-term use of antibiotics and chemicals to treat vibriosis and other diseases, antibiotic-resistance has widely spread among pathogens, leading to complicated developments of diseases, difficulties in treatment and the increasing antibiotic residues in the environment. Therefore, other preventive methods replacing the use of antibiotics is urgently needed. A potential approach is to interrupt the quorum sensing processes in vibrios. In this study, we investigated the method of electroporation for transferring pCR2.1QRR plasmid harbouring qrr-vibrio , a gene cluster designed previously that potentially inhibits quorum sensing in vibrios, into cells of Vibrio parahaemolyticus strain PAM17. The ratio of the number of plasmid-carrying colonies to the total number of grown colonies was 5/20, suggesting that the use of electroporation for the transfer is feasible. The recombinant strain almost lost its mobility, and its capability of forming a biofilm was 2-fold reduced in comparison with those of the origninal strain (the wild type) and the strain carrying only the vector. Thus, the results clearly showed a quorum-sensing inhibitory effect confered by qrr-vibrio .